E-Library Berbasis Mobile Bagi GPMB Kabupaten Malang Dalam Mendukung Gerakan Literasi di Era Pandemi COVID-19 - Setyorini Setyorini; Ike Kusdyah Rachmawati; Syarif Hidayatullah; Hutri Agustino (Institut Agama Islam Negeri (IAIN) Curup, 2022)
It is undeniable that during the Covid-19 pandemic all community activities are limited to direct interactions. One of the limits of activity is in the area of library services, where there are two services that libraries have to offer: physical lending and electronic lending. There are several barriers that libraries encounter in relation to e-book lending services. For example, low technical proficiency, limited equipment and infrastructure, internet network, and cost. Therefore, in order to solve these problems, we applied the method of user-centered design to system development, built a user-friendly and user-friendly mobile-based electronic library, and built visitor-library relationship management. The development of this library service system application uses a linear sequential method (waterfall). The waterfall methodology is a systematic, sequential software development method that starts at the system level and progresses through analysis, design, code, testing, and maintenance. Below are the stages of the waterfall model. E-library results have several features for restricting access rights, such as: B. Limitation on number of books and loan period. The resulting application has the main function of being able to protect your digital works in use. That is, restricting borrowed digital works to specific devices.